Shaping the University of the Future Using Technology to Catalyse Change in University Learning and Teaching - Marshall, Stephen James (Springer Singapore, 2018)
This book focuses on developing an understanding of the complex interplay of forces acting on individual universities and higher education systems to enable leaders and practitioners to take purposeful and strategic action. It explores the challenging landscape of higher education and the pressures that are reshaping the university as a societal institution, describing the complex interplay of technological, sociological, political and economic forces driving change. The issues analysed are global in scope, reflecting the diversity of contexts, but also the common nature of the challenges facing institutions individually and collectively. The analysis draws on the lessons learnt and evidence from over fifty organisational case studies undertaken by the author over the past decade, exploring organisational change in higher education institutions in New Zealand, Australia, the United States and the United Kingdom, and on his engagement as president of the ACODE organisation with colleagues responsible for learning technological change in Australasia. The book helps institutions respond to technological change purposefully, in ways that build upon a clear understanding of the complex nature of the existing institution, its students and the organisational context.